ANALISIS PENGELOLAAN KEUANGAN DESA DI NAGARI PADANG MAGEK KECAMATAN RAMBATAN KABUPATEN TANAH DATAR SAAT PANDEMI COVID-19 - Rahmadani, Erisa; Kawedar, Warsito (Diponegoro Journal of Accounting, 2024)
The Covid-19 pandemic has impacted all parties in all sectors of health, social and economy. Not only the impact on society and the business world, the government is also affected. The government as the center of the agency that serves the community is required to be able to cope with the Covid-19 pandemic and protect the people affected by the Covid-19 pandemic. Considering that the Covid-19 pandemic came in mid-March, it was necessary to focus on village funds that had been planned at the beginning of the year for handling the Covid-19 pandemic. The purpose of this study was to find out how the process of managing village finances in Nagari Padang Magek, Rambatan District, Tanah Datar Regency in the Covid-19 Pandemic era.The research method used in this study is a qualitative descriptive research method. With the technique of data collection is done by interview and documentation. The subjects in this study were village officials as actors in the financial management process and the community as parties who felt the benefits of village funds. Determination of this subject is done by purposive sampling method.The results showed that the 2020 budget financial management process in Nagari Padang Magek underwent changes due to the impact of the Covid-19 pandemic. This can be seen from the existence of several work program plans that had to be changed due to changes in regulations from the central government which caused village funds to be focused on handling the Covid-19 pandemic. However, the implementation process has been carried out optimally by complying with the applicable rules.